PENGGUNAAN MEDIA KARTU HURUF UNTUK MENINGKATKAN KEMAMPUAN MENGENAL HURUF ANAK USIA DINI - Retnaningrum, Wulandari; Lathifah, Inayatul (IAIIG Cilacap, 2020)
The media of early childhood learning generally use game tools to make it easier for children to understand something that night be difficult and simplify something complex and they can develop of their potential by the senses and experionces. The letter card media with rules is a kearning aid can make children get the opportunity to explore, make research and make experiments to gain knowledge. In learning to read in the beginning the teacher can use play strategies by utilizing letter cards. The letter card is used as a medium in the game of finding words. Students are invited to play by arranging letters into words based on puzzles or questions created by the teacher. The practice of arranging letters is the skill of spelling a word.